Wellness in the Light of the Eschaton: Reading the Psalms with Augustine - Ticciati, Susannah (Horizons in biblical theology, 2020)
This article considers wellness in terms of creaturely integrity, asking how the latter might be reconceived in the light of the eschaton. To that end, it draws on Augustine’s eschatological reading of the Psalms in his Enarrationes in Psalmos. It suggests that an eschatological vision reveals the “wholes” we habitually seek to be only partial wholes, which have a tendency to become “totalizing wholes.” Having offered an account of Augustine’s totus Christus hermeneutic, it turns to his interpretation of Psalm 30 (31), tracing it in terms of the paired concepts of opacity and transparency. It argues that the singing of the Psalms is, for Augustine, our present training in the transparency of the eschaton. It concludes by showing how such an eschatological orientation inculcates a posture humble courage, in which totalizing wholes are critiqued as previously overlooked creaturely connections come into view.